Design of a randomised, double-blind, crossover, placebo-controlled trial of effects of sildenafil on cerebrovascular function in small vessel disease: Oxford haemodynamic adaptation to reduce pulsatility trial (OxHARP) - Webb, A; Werring, D; Dawson, J; Rothman, A; Lawson, A; Wartolowska, K (SAGE Publications, 2021)
Background Cerebral small vessel disease (SVD) is associated with increased cerebrovascular pulsatility, endothelial dysfunction, and impaired vascular reactivity. Vasodilating phosphodiesterase inhibitors may improve cardiovascular pulsatility and reactivity, and potentially reduce progression of SVD.